Da bambini intorno al Millenovecento. Frammenti d’infanzia nelle riflessioni di Walter Benjamin - Lazzarini, Anna (Studi sulla Formazione/Open Journal of Education, 2016)
The text aims at analyzing the complex and refined anthropology of childhood that takes shape in the pages of Walter Benjamin. This anthropology of childhood is deeply rooted in his memories of child “around 1900” and is patiently reconstructed from the picture books, from the games and the vintage toys, from the images and the characters that fill fantastic stories and fairy tales, from domestic and family rituals, from the world of objects and atmospheres of the bourgeois intérieur, Above all, this anthropology brings to light images. These images have a peculiar feature, a distinctive sign: they seem brought together by the idea and the experience of the threshold, a crucial figure in the epistemology of Benjamin.